5G NR - The Next Generation Wireless Access Technology (2nd Edition) - Dahlman, Erik; Parkvall, Stefan; Skold, Johan (Elsevier, 2021)
This book follows the authors' highly celebrated books on 3G and 4G and provides a new level of insight into 5G NR. After background discussion of 5G, including requirements, spectrum aspects, and the standardization timeline, all technology features of the first phase of NR are described in detail. The book covers the NR physical-layer structure and higher-layer protocols, RF and spectrum aspects, and co-existence and interworking with LTE. The book provides a good foundation in NR and different NR technology components, giving insight into why a certain solution has been selected. This second edition is updated to reflect the latest developments in Release 16 and includes brand new chapters on: NR in unlicensed spectrum; NR-U in Rel-16; IAB; V2X and sidelink in Rel-16; industrial IoT; IIoT and referring to the URLLC enhancements for PDCCH; RIM/CL; and positioning.